A COMPREHENSIVE REVIEW ON SYNTHESIS, PROPERTIES, AND APPLICATIONS OF CDS/AG-DOPED POLYVINYL ALCOHOL (PVA) NANOCOMPOSITES - Abdulelah, Haider; Radh, Wisam A.; Dheyab, Raed A. (PT ANTIS INTERNATIONAL PUBLISHER, 2026)
Objective: Nanoparticle addition in the polymer matrix is a recent development in the materials science whereby composite materials are produced with special properties that are superior to that of the material used. Special attention has been given to nanocomposites made on polyvinyl alcohol (PVA) which involve nanoparticles of silver (Ag) and cadmium sulphide (CdS). The review will entail a critical review of the recent innovations in the synthesis procedures of PVA nanocomposites with CdS and Ag doping. Method : The techniques employed in determining the significant changes in mechanical, optical, electrical and structural characteristics of the components are SEM, FTIR, XRD and UV-VIS spectroscopy. Results : A substrate is a great polymer that is soluble in water, biodegradable and exceedingly flexible: PVA has a large density of functional hydroxyl groups that stabilize the nanoparticles, in addition, it has a good chemical stability as well as forming a film. CdS is a top quality tunable bandgap II- VI semiconductor that possesses excellent optical and photocatalytic characteristics. Electrical conductivity and antimicrobial action of silver nanoparticles (SPs) in the form of plasmonics are specifically impressive. The Ag and CdS in a PVA matrix is a multi-purpose nanocomposite with improved and variousiated functions. Besides, the review also takes a closer look at the growing uses of these nanocomposites in other industrial fields such as the flexible optoelectronics (e.g. 3). H. photodetectors, antimicrobial coats, radiation shielding, photocatalytic de-pollutionants, light-emitting diodes based on LED. Lastly, an argument is made on the present challenges and opportunities in the development and implementation of these innovative functional materials. Novelty : The Ag and CdS in a PVA matrix is a multi-purpose nanocomposite with improved and variousiated functions.